Dome shaped array of pressure sensors for underwater flow sensing and object detection - Kanhere, Elgar Vikram (2018)
Autonomous underwater vehicles (AUVs) play a critical role in underwater surveys and explorations, which are beneficial to commercial sectors like oil and gas industry and scientific research disciplines like oceanography. AUVs rely on acoustic and optical sensing systems to be aware about their surroundings. However, the applicability of these conventional sensing systems is hindered in dark and turbid waters. Passive mechanoreception provides an alternative approach to overcome the limitations of conventional sensing systems, which assists in gathering information about surroundings by discerning flows and disturbances in the vicinity of AUVs. This work is an attempt to develop a passive mechanoreceptive system by drawing inspiration from the mechanosensory expertise of crocodiles.